An empirical invistigation of determinants associated with audit report lag in Jordan - Aljaaidi, Khaled Salmen; Bagulaidah, Ghassan Saeed; Ismail, Noor Azizi; Fadzil, Faudziah Hanim (University of Jordan, 2015)
This paper examines whether external auditor's reliance on the work of internal audit function and audit committee's characteristics are associated with audit report lag.We posit that an effective audit committee and more reliance on the work of client's internal auditor reduce external audit efforts, thus reducing audit report lag. Data was obtained from 87 survey respondents (external auditors) of listed companies in Amman Stock Exchange (ASE) in Jordan and annual reports of the respective firms for the year 2009. Ordinary Least Square (OLS) regression analysis show that, an active audit committee (more frequent meetings) and a high percentage of reliance on the work of internal audit function by the external auditors are associated with shorter audit report lag.The results of this study would offer important implications to accounting and auditing policy makers, ASE, external auditors and Jordanian public companies.